Cobaltoceniumselenolate Gold(I) Complexes: Synthesis, Spectroscopic, Structural and Anticancer Properties. Issue 27 (15th June 2021) - Menia, Daniel; Kopacka, Holger; Wurst, Klaus; Müller, Thomas; Lippmann, Petra; Ott, Ingo; Bildstein, Benno
Abstract: Cobaltoceniumselenolate is an unusual, highly air‐sensitive, mesoionic compound containing a very soft anionic selenium donor atom. Here we explore its coordination chemistry with Au(I) metal centers and show that its hetero‐ and homoleptic gold complexes are highly colored, air‐stable compounds, which were characterized by 1 H/ 13 C/ 31 P/ 77 Se NMR, IR, UV‐Vis, HR‐MS and single crystal XRD. Cytotoxicity of these polar, water‐soluble complexes was studied against various standard cancer cell lines (A549MDA‐MB‐231, HT‐29) revealing good anticancer activity of all three complexes. Abstract : Air‐stable homo‐ and heteroleptic gold(I) complexes containing the unusual zwitterionic cobaltoceniumselenolate ligand were synthesized and fully characterized. First preliminary biological test against three standard human cancer cell lines showed good cytotoxicity properties, indicating that cobaltocenium selenolate is a promising ligand for future developments of redox‐active organometallic metallo‐drugs for anticancer therapy.